Large changes in carbon storage under different land-use regimes in subtropical seasonally dry forests of southern South America - Conti, Georgina (2014)
Net emissions of CO2 from land-use conversion represent a significant driver of global climatic change. This is especially true for subtropical seasonally dry Chaco forests from southern South America, now experiencing one of the highest loss rates globally. However, direct quantifications of the effect of accelerated deforestation on carbon (C) pools of these systems are rare. Considering five dominant ecosystem types within the dry Chaco forest of Argentina, derived by land-use change from the same original vegetation, substrate, and climate, we quantified the magnitude and change of total C pools including trees and shrubs, non-woody plants, coarse and fine debris, and soil organic (SOC) and inorganic (SIC) pools up to 2 m depth. Soil C pools represented the largest C stocks (>74%). Shrubs also represented a large C pool (at least 28% of the aboveground standing biomass), which we quantified in detail for the first time. The conversion of forests to open shrublands and croplands was associated to large losses of organic C both in aboveground biomass and in soils down to 30 cm depth (from 43 to 64%). Although SIC is usually considered as a relatively stable compartment, the forest to crop transition presented here involved carbonate losses of c. 68% at soil depths between 1 and 2 m. Our results indicate that the landscape transformations expected in the region under business-as-usual socioeconomic scenarios will probably lead to a marked reduction of the C stored, with a consequent net C emission and a decline in other C storage-related ecosystem services provided by these ecosystems.